Comparative study the essential oil composition of flowers and leaves of Crataegus Monogyna L. - Sydora, N.; Konovalova, O.; Zuikina, S.; Semchenko, K.; Rudnyk, A.; Hurtovenko, I.; Рудник, Анна Михайлівна (My University, 2021)
The aim of the work was to obtain essential oil from the leaves and flowers of the genus Hawthorn Crataegus monogyna L. and study its component composition to justify the possibility of expanding the use of this herbal drugs in medicine. Materials and methods. The leaves and flowers of Сrataegus monogyna L., which were used to obtain essential oil, were harvested in the western region of Ukraine in 2019. The quantitative content of essential oil in the herbal drugs was determined by hydrodistillation. By used chromato-mass spectrometry method determined the component composition of essential oil of leaves and flowers of Сrataegus monogyna L. The obtained spectra were compared with the library of mass spectra NIST05 and WILEY 2007 with a total number of spectra over 470000 in combination with programs for identification AMDIS and NIST. Results. The essential oil of leaves and flowers of Сrataegus monogyna L. was obtained and its quantitative content was determined, which was 0.15±0.02 % for flowers and 0.11±0.03 % for leaves. By used chromato-mass spectrometric method in the essential oil of flowers of Сrataegus monogyna L. revealed 37 compounds, leaves – 33. In the essential oil of flowers found monoterpenoids, the content of which was 0.44 % of the total, triterpenoids 7.17 %, aromatic compounds 12.61 %. In the essential oil of leaves were found monoterpenoids 37.8 %, aromatic compounds 10.25 %, norterpenoids 3.62 %, sesquiterpenoids 4.02 %, diterpenoids 2.17 %, triterpenoids 5.08 %. Conclusions. Due to the defined component composition of the essential oil of flowers and leaves of Сrataegus monogyna L., we consider its use to create drugs of external action for the treatment of skin diseases of various etiologies caused by staphylococcal and fungal microflora
Keywords: hawthorn; leaves; flowers; essential oil; quantitative content; chemical composition